Antibiotic Treatment of Community-Acquired Pneumonia in Hospitalized Patients in Argentina (2010–2015). (4th October 2017) - Curcio, Daniel; Cane, Alejandro
Abstract: Background: Community-acquired pneumonia (CAP) is generally considered to be a major cause of morbidity and mortality which, in the majority of cases, needs an antibiotic intervention. The aim of this study was to identify the antibiotics prescription patterns for adults hospitalized with CAP in Argentinean hospitals. Methods: This hospital-based, descriptive epidemiological study was performed using data from a large Argentinean health insurance database by searching for codes for CAP as discharge diagnosis ( International Classification of Diseases -10) (January 1 st 2010-November 30, 2015). The study population was adults (≥18 years old), who had been treated with antibiotics for ≥3 days. A conditional logistic regression was used to identify variables significantly associated with multi-morbidity (MM) (≥2 risk factors/co-morbidities significantly associated to CAP). Results: Of the 2247 adults hospitalized with CAP, data for 1697 (75.5%) patients was eligible for inclusion in the analysis (1292 [76%], ≥65 years old). The most frequently prescribed antimicrobial regimen was β-lactam/β-lactamase inhibitors and macrolides in combination (21.6%), followed by monotherapy regimens: macrolides (14.0%), β-lactam/βlactamase (11.3%), fluoroquinolones (FQ) (11.3%), and third-generation cephalosporins (3gC) (7.5%). Patients ≥65 years old were identified as significantly associated with MM ( risk stacking ) ( P = 0.0000); intensive care unit admission ( P = 0.0000); ≥7 days of antibiotic treatment ( P = 0.0040); use the antibiotic other than β-lactam/β-lactamase inhibitors (3gC, FQ and macrolides) ( P = 0.0070); and combination therapy ( P = 0.0211). Conclusion: Global patterns of antimicrobial prescription for adult patients hospitalized with CAP in Argentinean hospitals were in concordance with national/international evidence based guidelines. The sub-group of older patients (≥65 years old) is associated with long-duration therapy and broad-spectrum antibiotic use, including those related to the selection and emergence of multi-drug resistance pathogens (3gC and FQ). Prevention strategies for CAP such us pneumococcal and influenza vaccination recommendations have to be consider as part of antimicrobial stewardship strategy. Disclosures: D. Curcio, Pfizer: Employee,  Salary; A. Cane, Pfizer: Employee, Salary